The Feasibility of a Mini Dictionary of Literary Text Terms as a Learning Medium for Class XI Students at Al-Washliyah 1 Senior High School Medan - Devi Fitriani Sitompul; Rika Kartika; Ratna Soraya (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aimed to develop a Mini Dictionary of Literary Text Terms as a learning medium for Class XI students at Al-Washliyah 1 Senior High School Medan to improve their understanding of literary concepts and terminology. Methodology: This study employed the Research and Development (R&D) method, following the Borg and Gall development model. Data collection involved observation and questionnaires. The study included 62 students from Class XI Science and Social Science streams, with a sample of 31 students from Class XI Science. Expert validation assessments were conducted by two material experts, two design experts, and a teacher. Main Findings: Validation results from Material Expert I (92%) and Material Expert II (77%) classified the dictionary as